PHOSPHATE REMOVAL BY OCEANIC HYDROTHERMAL PROCESSES: AN UPDATE OF THE PHOSPHORUS BUDGET IN THE OCEANS - Wheat C.G.; Feely R.A.; Mottl M.J. (My University, 1996)
We present a compilation of dissolved phosphate and solid-phase P data from the oceanic crust to evaluate the effects of hydrothermal processes on the oceanic budget of P. Concentrations of phosphate in fluids that emanate from ridge-axis hydrothermal systems are less than that in bottom seawater. The extent of removal in these fluids is at least 30% and in some hydrothermal systems dissolved phosphate is removed completely from the circulating fluid. Evidence for the removal of phosphate in each of six ridge-flank hydrothermal systems is based on systematic variations in porewater profiles of phosphate and speeds of porewater flow. The extent of removal is > 80% in these ridge-flank systems. These removal processes are recorded in the basaltic crust as an increase in P concentration that coincides with an increase in extent of alteration and content of ferric iron. Phosphate also is removed in hydrothermal plumes by coprecipitation with Fe oxyhydroxide particles, which eventually deposit on the seafloor.Each of these hydrothermal processes results in a flux of P into the oceanic crust. Bottom seawater flow through ridge-axis hydrothermal systems removes at most 0.4% of the preindustrial dissolved riverine flux of P, while ridge flanks remove at least 5%, but less than 50% of the dissolved riverine flux, consistent with P data from Deep Sea Drilling Project (DSDP) Sites 417 and 418. Removal of phosphate by coprecipitation with Fe-rich particles in hydrothermal plumes along ridge axes accounts for 18-33% of the dissolved riverine flux. Thus, hydrothermal systems remove about 50% of the preindustrial dissolved riverine flux of phosphate. We have included these new estimates in a revised budget for oceanic P.